COVID-19 and Basic Need Insecurities: How Administrators Addressed BNI During and Beyond the Pandemic - Dayna Prochaska; Robert Exley (Educational Considerations, 2025)
Basic need insecurities (BNI) often impact the ability of community college students to persist and complete their goals. The COVID-19 pandemic exacerbated BNI for students, forcing administrators to address BNI. The purpose of this study was to gain a deeper understanding of the leadership strategies and competencies that contributed to how administrators responded to BNI during the COVID-19 pandemic and to identify the changes that were implemented to support community college students in Texas during this time. The study found that demonstrating compassion and care to students and employees; establishing open, clear, concise, and constant communication; collaborating and empowering employees with knowledge and tools were vital for addressing students' BNI during the pandemic. The most impactful implementation was the creation of a one-stop shop where wrap-around services were provided to address BNI, including mental health, food pantries, clothes closets, personal hygiene products, childcare, transportation, emergency aid, and housing assistance.
Keywords: Basic Need Insecurities; COVID-19 Pandemic; Services; Community Colleges; Leadership Competencies